1998
DOI: 10.1111/j.1550-7408.1998.tb05073.x
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Ca2+ Homeostasis in Trypomastigotes of Trypanosoma cruzi

Abstract: Trypomastigotes of Trypanosoma cruzi maintain an intracellular Ca2+ concentration ([Ca2+]i) of 64 +/- 30 nM. Equilibration of trypomastigotes in an extracellular buffer containing 0.5 mM [Ca2+]o (preloaded cells) increased [Ca2+]i < 20 nM whereas total cell Ca2+ increased by 1.5 to 2.0 pmole/cell. This amount of Ca2+ would be expected to increase [Ca2+]i to > 10 microM suggesting active sequestration of Ca2+. We tested the hypothesis that maintenance of [Ca2+]i involved both the sequestration into intracellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Thapsigargin and IP 3 were not able to affect the vanadate-sensitive Ca 2+ transport. Such an effect of digitonin has been attributed, in some cases, to the cell growth medium composition (Zhang et al 1998 ;Miranda et al 2005). No evidence of a third Ca 2+ compartment with the characteristics of the acidocalcisomes described by Vercesi et al (1994) was observed in those experiments.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Thapsigargin and IP 3 were not able to affect the vanadate-sensitive Ca 2+ transport. Such an effect of digitonin has been attributed, in some cases, to the cell growth medium composition (Zhang et al 1998 ;Miranda et al 2005). No evidence of a third Ca 2+ compartment with the characteristics of the acidocalcisomes described by Vercesi et al (1994) was observed in those experiments.…”
Section: Introductionmentioning
confidence: 85%
“…Discrepancies between experiments have been attributed to an undesirable effect of digitonin solubilizing the membranes rather than the cytoplasm. Such an effect of digitonin has been attributed, in some cases, to the cell growth medium composition (Zhang et al 1998; Miranda et al 2005).…”
Section: Introductionmentioning
confidence: 99%